2018
DOI: 10.1172/jci.insight.97918
|View full text |Cite
|
Sign up to set email alerts
|

Absence of ANGPTL4 in adipose tissue improves glucose tolerance and attenuates atherogenesis

Abstract: Alterations in ectopic lipid deposition and circulating lipids are major risk factors for developing cardiometabolic diseases. Angiopoietin-like protein 4 (ANGPTL4), a protein that inhibits lipoprotein lipase (LPL), controls fatty acid (FA) uptake in adipose and oxidative tissues and regulates circulating triacylglycerol-rich (TAG-rich) lipoproteins. Unfortunately, global depletion of ANGPTL4 results in severe metabolic abnormalities, inflammation, and fibrosis when mice are fed a high-fat diet (HFD), limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 63 publications
11
109
2
1
Order By: Relevance
“…We have observed that adipose-specific ANGPTL4 knockout (Ad-KO) mice displayed reduced circulating TAG levels, similar to what was observed in humans with a missense mutation in ANGPTL4 (E40K variant). However, other factors identified in this study such as body weight and regulation of glucose homeostasis, were unaltered after chronic administration of HFD feeding (32). These findings suggest that ANGPTL4 in other tissues, such as the liver, could also play a key role in the regulation of whole-body metabolism.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…We have observed that adipose-specific ANGPTL4 knockout (Ad-KO) mice displayed reduced circulating TAG levels, similar to what was observed in humans with a missense mutation in ANGPTL4 (E40K variant). However, other factors identified in this study such as body weight and regulation of glucose homeostasis, were unaltered after chronic administration of HFD feeding (32). These findings suggest that ANGPTL4 in other tissues, such as the liver, could also play a key role in the regulation of whole-body metabolism.…”
Section: Introductionmentioning
confidence: 54%
“…Our recent work has demonstrated an essential role for adipose-derived ANGPTL4 in regulating lipid uptake and regulation of metabolic function by AT (32). We have observed that adipose-specific ANGPTL4 knockout (Ad-KO) mice displayed reduced circulating TAG levels, similar to what was observed in humans with a missense mutation in ANGPTL4 (E40K variant).…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations